2021
DOI: 10.2337/db21-761-p
|View full text |Cite
|
Sign up to set email alerts
|

761-P: Safety and Pharmacokinetic Study of GPR40 Agonist (CPL207280) after a Single Dose in Healthy Subjects

Abstract: Activation of GPR40 (G-protein coupled receptor 40) in pancreatic β-cells may improve glycaemic control in type 2 diabetes (T2D) patients through enhancement of glucose-stimulated insulin secretion (GSIS). Here we present phase I an open label, dose-escalation study with single oral administration of GPR40 agonist - CPL207280 in healthy subjects in fasting conditions. The study was performed in conventional 3+3 design, where MTD (maximum tolerated dose) is to be determined. Caucasian male and female subjects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The median T max ranged from 1 to 3 h after administration 16 and did not seem to be dose‐dependent (Table S3). A single outlier for the dose 240 mg was observed with a T max of 16 h. C max and AUC 0–24h increased in each consecutive cohort.…”
Section: Resultsmentioning
confidence: 98%
“…The median T max ranged from 1 to 3 h after administration 16 and did not seem to be dose‐dependent (Table S3). A single outlier for the dose 240 mg was observed with a T max of 16 h. C max and AUC 0–24h increased in each consecutive cohort.…”
Section: Resultsmentioning
confidence: 98%
“…Combination of TGR5 agonist, DPP4 inhibitor, and SSTR5 antagonist showed a robust suppression in both oGTT and ipGTT in GIP-deficient mice. These effects were mediated by GLP-1 as blocking GLP-1 receptor abolished the efficacies (Briere et al, 2018). In line with this finding, Jespen et al showed glucose-stimulated GLP-1 secretion was enhanced in mice deficient in SSTR5 or treated with SSTR5 antagonist (Jepsen et al, 2021), and SSTR5 antagonist and DPP4 inhibitor synergistically increased GLP-1 and improved oral glucose tolerance in mice (Liu et al, 2018;Jepsen et al, 2021).…”
Section: Gut-restrictive Gpr40 Agonist For Metabolic Disorders and Be...mentioning
confidence: 88%
“…Phase I trial of CPL207280 was safe and well tolerated with no serious AEs in healthy participants. No dose limiting toxicity was observed at up to 480 mg (Bazydlo-Guzenda et al, 2021c). CPL207280 is now under development in phase II trial for T2D (ClinicalTrials identifier NCT05248776, 2022).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations